Management of Phaco complications newer techniques - Agarwal, Amar (Jaypee - Highlights Medical Publishers, 2014)
Cataracts are a very common condition whereby the lens of the eye becomes cloudy causing blurred vision. Over time, a cataract can get worse, eventually leading to blindness if untreated. Cataracts are the most common cause of blindness worldwide. Phacoemulsification surgery is the most widely used method for cataract management.